SUBJECT OF A CRIMINAL OFFENCE AS PART OF ILLEGAL HUNTING (Bulletin of criminological association of Ukraine, 2024)
The constant reduction of the animal component of the ecological system, especially now, under the influence of the full-scale invasion of the Russian Federation, creates significant threats to environmental safety as an element of Ukraine's national security. The article is devoted to clarifying the features of individual items of illegal hunting and providing proposals aimed at improving the theoretical provisions and practice of their application in the qualification of criminal offenses against the environment. The main debatable issues existing in the theory of criminal law and gaps in legal practice regarding conceptual differences, interconnection and correlation of the subject and object of illegal hunting are analyzed. Attention is focused on the existence of an urgent need to detail the subject of the criminal offense, the responsibility for which is provided for by Art. 248 of the Criminal Code of Ukraine "Illegal hunting". The need to develop effective mechanisms for ensuring criminal law protection of the rational use and reproduction of fauna is summarized, considering the damage caused because of armed aggression by the Russian Federation.
Keywords: illegal hunting; subject of a criminal offense; social relations; fauna; ecological system; environment; natural resources; martial law; war; combating crime